Intellectual Property, the Banking Crisis and the Public Interest - KINGSTON, WILLIAM (Thomson Reuters / Sweet and Maxwell, 2011)
The UK Hargreaves inquiry is one more testimony to the failure of intellectual property laws to deliver the innovation that is their only justification. This parallels numerous similar investigations of the worldwide banking crisis. Yet both failures have an easily understood common cause: the making of property laws has been allowed to fall into the hands of those who benefit from them. Since capitalism can only work by denying capitalists the power to set their own working conditions, the crucial question for any reform is: who can now speak for the public interest in these kinds of legislation?
PUBLISHED
Keywords: Economics; Intellectual Property; Banking Crisis; Hargreaves Inquiry